Circuits and functions of the lateral habenula in health and in disease - Hu, Hailan; Cui, Yihui; Yang, Yan (Nature reviews. Neuroscience, 2020)
The past decade has witnessed exponentially growing interest in the lateral habenula (LHb) owing to new discoveries relating to its critical role in regulating negatively motivated behaviour and its implication in major depression. The LHb, sometimes referred to as the brain’s ‘antireward centre’, receives inputs from diverse limbic forebrain and basal ganglia structures, and targets essentially all midbrain neuromodulatory systems, including the noradrenergic, serotonergic and dopaminergic systems. Its unique anatomical position enables the LHb to act as a hub that integrates value-based, sensory and experience-dependent information to regulate various motivational, cognitive and motor processes. Dysfunction of the LHb may contribute to the pathophysiology of several psychiatric disorders, especially major depression. Recently, exciting progress has been made in identifying the molecular and cellular mechanisms in the LHb that underlie negative emotional state in animal models of drug withdrawal and major depression. A future challenge is to translate these advances into effective clinical treatments. The lateral habenula (LHb) has received increasing attention in part because dysfunction of this region may play a part in several psychiatric disorders, notably depression. In this Review, Hu et al. examine the neural circuits, physiological functions and potential pathophysiological roles of the LHb.